Safety and precision of frontal trajectory of lateral habenula deep brain stimulation surgery in treatment-resistant depression - Cui, Zhiqiang; Jiang, Chao; Hu, Chunhua; Tian, Ye; Ling, Zhipei; Wang, Jian; Fan, Tengteng; Hao, Hongwei; Wang, Zhiyan; Li, Luming (Frontiers in Neurology, 2023)
Introduction The lateral habenula (LHb) is a promising deep brain stimulation (DBS) target for treatment-resistant depression (TRD). However, the optimal surgical trajectory and its safety of LHb DBS are lacking. Methods We reported surgical trajectories for the LHb in six TRD patients treated with DBS at the General Hospital of the Chinese People's Liberation Army between April 2021 and May 2022. Pre-operative fusions of magnetic resonance imaging (MRI) and computed tomography (CT) were conducted to design the implantation trajectory of DBS electrodes. Fusions of MRI and CT were conducted to assess the safety or precision of LHb DBS surgery or implantable electrodes locations. Results Results showed that the optimal entry point was the posterior middle frontal gyrus. The target coordinates (electrode tips) were 3.25 ± 0.82 mm and 3.25 ± 0.82 mm laterally, 12.75 ± 0.42 mm and 13.00 ± 0.71 mm posterior to the midpoint of the anterior commissure–posterior commissure (AC-PC) line, and 1.83 ± 0.68 mm and 1.17 ± 0.75 mm inferior to the AC-PC line in the left and right LHb, respectively. The “Ring” angles (relative to the AC-PC level on the sagittal section plane) of the trajectories to the left and right LHb were 51.87° ± 6.67° and 52.00° ± 7.18°, respectively. The “Arc” angles (relative to the midline of the sagittal plane) were 33.82° ± 3.39° and 33.55° ± 3.72°, respectively. Moreover, there was small deviation of actual from planned target coordinates. No patient had surgery-, disease- or device-related adverse events during the perioperative period. Conclusion Our results suggested that LHb-DBS surgery via frontal trajectory is safe, accurate, and feasible. This is an applicable work to report in detail the target coordinates and surgical path of human LHb-DBS. It has of great clinical reference value to treat more cases of LHb-DBS for TRD.